Effects of Boesenbergia rotunda (L.) Mansf. on sexual behaviour of male rats - Paiwan Sudwan (2018)
Aim: To study the effects of Boesenbergia rotunda (Krachai) on sexual behaviour in male albino rats. Methods: Thirty-two male Wistar rats were equally divided into four groups: experimental groups were gavaged with the ethanolic extract of the rhizome of B. rotunda at doses of 60, 120 and 240 mg/kg and a control group received distilled water, for 60 days. Sexual behaviour, reproductive organs, diameter of seminiferous tubule, epididymal sperm density, and androgenic hormones were evaluated. Results: Within 30-minobservation, there was no significant difference of courtship behaviour, mount frequency (MF), intromission frequency (IF), mount latency (ML), intromission latency (IL), copulatory efficiency or intercopulatory interval in male rats. In three 10-min intervals over a 30-min period, courtship behaviour and MF during the first 10-min were significantly higher than those in the second and third 10-min observation in all groups, whereas IF had no significant difference. All doses of B. rotunda extract significantly increased the relative testicular weight and the diameter of the seminiferous tubules. The dose of 60 mg/kg also significantly increased the relative weight of the seminal vesicle. Nevertheless, the sperm density, serum testosterone and androstenedione levels were not affected by the B. rotunda extract. Conclusion: B. rotunda does not affect sexual behaviour nor serum androgenic levels. © 2007 Asian Journal of Andrology, Shanghai Institute of Materia Medica, Chinese Academy of Sciences.